Air Conditioner Customer Retention Based on Satisfaction and Loyalty with A Marketing Mix Analysis - Andrew Wijaya; Harvani Aprilia Tan; Ruby Merrey Tanoro; Bambang Suwarno; Shaista Noor (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The purpose of this research is to examine the relationship between customer satisfaction and retention for air conditioners (ACs) sold in retail stores in Medan, as well as the impact of the marketing mix. This quantitative study surveyed 1,614 AC buyers from 14 retail stores in Medan (May–September 2025) and analyzed the data using PLS-SEM to test validity, reliability, and hypothesis significance. The results show that all four marketing mix variables significantly affect customer satisfaction, with place (store location and accessibility) having the strongest influence, followed by price and product, while promotion negatively affects satisfaction. Customer satisfaction strongly predicts loyalty, and loyalty significantly influences customer retention. The mediation analysis confirms that loyalty and satisfaction together enhance the effects of marketing mix variables on retention, although promotional efforts can reduce satisfaction and weaken retention when poorly executed. By examining the air conditioner market in Indonesia through the 4P marketing mix framework and the satisfaction-loyalty-retention linkages in the retail sector, this study adds to the marketing literature. The results shed light on an understudied aspect of retention in the air conditioner market—the importance of store accessibility and customer experience—and provide managers with insight into how to optimize location, service, and value-based strategies rather than relying solely on price or promotion. These findings suggest that management needs to focus on strategic locations and quality service to improve customer satisfaction. Businesses are advised to shift from aggressive promotions to value strategies such as after-sales service and loyalty programs.